30 Seconds Sit-To-Stand Test: Reference Values for the Chilean Population - Jadue-Flores, L (Sociedad Medica de Santiago, 2025)
Assessment of functional capacity is essential for identifying mobility issues and tailoring rehabilitation strategies. The 30-seconds sit-to-stand test (30s-STST) is valid and reliable for evaluating lower limb muscle. Aim: To establish reference values for the 30s-STST in adults aged 18-80 years in the Chilean population. Methods: A cross-sectional study was conducted across six centers in Chile, three were universities and the other three were family health centers. The anthropometric variables, levels of physical activity, smoking status, and the number of repetitions during the 30s-STST were recorded. To establish the reference values, we calculated sex-and age-specific normative percentiles (2.5th, 10th, 25th, 50th, 75th, 90th, and 97.5th) for six different age groups. Additionally, multiple linear regression analyses were performed separately for men and women, with performance in the 30s-STST as the dependent variable and age, height, and weight as predictors. Results: Four hundred ninety-nine individuals were included in the study (57.5% women). The median (25th-75th percentile) number of repetitions in women was: 18-29 years: 19 (17-24), 30-39 years: 20 (18-23), 40-49 years: 17 (15-20), 50-59 years: 16 (14-20), 60-69 years: 15 (12-19), 70-80 years: 13 (11-18). While in men it was: 18-29 years: 19 (16-24), 30-39 years: 21 (18-27), 40-49 years: 16 (1524), 50-59 years: 18 (16-21), 6 0-69 years: 14 (12-15), 70-80 years: 11 (10-13). The predictive equations are as follows: Men: 30s-STST= 25.364 - (age years * 0.158); Women: 30s-STST= 39.264 - (age years * 0.136) - (height cm * 0.095). Conclusions: This study successfully established reference values for the adult Chilean population, which can be used as a reference in other Southern Cone populations, given the shared regional characteristics. © 2025, This is an Open Access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.